STEM-5E Integration and Local Wisdom of Geblek Making in Physics E-Books: Its Impact on Students' Digital Literacy Profiles - Supahar; Reny Afifah; Ayu Mar'ati Barokatun Ni'mah (Universitas Muhammadiyah Makassar, 2026)
In modern physics education, digital literacy has shifted from a supplementary skill to an essential competency for meaningful scientific inquiry. However, despite widespread access to digital technology, many students still demonstrate limited academic digital literacy, especially in physics learning contexts. This study aims to examine the effects of an interactive physics e-book integrated with the STEM 5E learning cycle and the local wisdom of geblek-making on students’ digital literacy profiles. A quasi-experimental pretest–posttest control group design was used, involving 108 grade X students divided into an experimental group (STEM-5E e-book), a contrast group using a 3E e-book, and a contrast group using traditional textbooks. Students’ digital literacy, including information literacy, media literacy, and ICT literacy, was measured with a validated 14-item multiple-choice test and analyzed using Aiken’s V and Rasch modeling. Results show that the experimental group achieved the greatest improvement, with a mean normalized gain of 67.33% (moderately effective), outperforming the 3E group (55%) and the traditional group (44.67%). Information literacy showed the most notable improvement, reaching an effective category with an 82% increase. Rasch-based profile analysis also revealed the complete removal of low levels of digital literacy in the experimental group. The novelty of this study lies in its integration of ethnoscience with the STEM-5E framework via an interactive digital medium, positioning digital literacy as a culturally rooted skill. In conclusion, the findings show that combining inquiry-based learning, interactive digital tools, and local wisdom offers an effective way to enhance students’ digital literacy and provides a strong pedagogical model for developing 21st-century skills in physics education.